Thin Capitalization Rules in EU Member States - Tatjana Ðukić (Central European Public Administration Review)
Thin capitalization rules fit in the group of the specific anti-avoidance rules (SAAR) which are legalised by domestic tax laws. Anti-avoidance measures attempt to strike down unacceptable tax avoidance practices that have taken place with the increasing importance of multinational firms. In contrast to local firms, multinational corporations can shift profits to lower taxed foreign locations, leading to substantial losses in tax revenue. The article presents a systematic review of thin capitalization rules in EU 27, summing up four most common approaches of thin capitalization regulation. The analysis revealed that the majority of countries (15) legalised the fixed ratio approach, one quater (7) the subjective approach and only a few (3) legalised the hidden profit distribution. Two of them have improved thin-cap rules to so called earningstripping rule.